E-Learning Satisfaction Menggunakan Metode Auto Model - Arif Rinaldi Dikananda; Fidya Arie Pratama; Ade Rizki Rinaldi (Politeknik Harapan Bersama, 2019)
E-Learning just like learning media in general need to be evaluated to find out and measure how much effectiveness, efficiency and user satisfaction with the quality of the overall learning process. One effort that can be done to find out and evaluate the quality of a learning is to use satisfaction evaluation. Measurement of satisfaction requires data derived from questionnaires that are presented using a Likert scale. The data illustrates the perception of users who have uncertainty because it is very subjective so that it has the potential to cause misinterpretation. The auto model method can be used to evaluate e-Learning satisfaction because the auto model method has the advantage of solving a problem with the various models produced, which in this case are in accordance with the context of the satisfaction problem that is often presented in natural language that has uncertainty, such as